Valid, Practical, and Effective Numeracy Literacy Module for 5th Grade Students - Romla, Siti; Wardana, Mahardika Darmawan Kusuma (Inquest Journal, 2024)
This study aims to develop a numeracy literacy-based learning module for 5th-grade elementary school students to support the independent curriculum. Using the ADDIE model, the module underwent rigorous validation, practicality, and effectiveness testing. Results indicate high validity (89.45%), practicality (95.6%), and effectiveness in improving students' learning outcomes. The module's implementation can enhance students' understanding of numeracy concepts and support their learning under the independent curriculum. Implications include the potential for further development of similar modules for other subjects and exploration of digital formats to improve accessibility for students.